PEDAGOGICAL AND PSYCHOLOGICAL POTENTIAL OF ASMR AS A LEARNING TOOL IN EDUCATIONAL SETTINGS FOR CHILDREN’S AND STUDENTS’ MENTAL AND SOCIAL WELL-BEING - Georgieva-Hristozova, Violeta (International Journal of Innovative Technologies in Social Science, 2023)
The aim of the theoretical framework is to examine the issue of autonomous sensory meridian response (ASMR) among scientific communities and enhance the knowledge horizons of students in medical and pedagogical fields. Considering the increasing public interest in ASMR, the article also addresses the parents of ASMR content consumers. The material reviews the current international research on ASMR and its effects on children and students. Using scientific methods of theoretical analyses, observation, and expert evaluation, the author popularizes in the specialized media the specifics and psycho-pedagogical effects of ASMR on the people who shape the generation Z and generation Alpha. The results highlight the need for in-depth theoretical and empirical research in order to gain a better understanding of the impact of ASMR on the mentioned young generations. Such research is crucial for establishing the connection between ASMR and mental health and socialization in these groups, as well as for understanding the relationship of the phenomenon under investigation with the existing scientific knowledge. Concerns regarding adverse consequences on the mental health and socialization of children and students are also shared.